Evaluasi Penerapan Sistem Peringatan Dini Bencana Longsor di Kampung Jatiradio, Desa Cililin, Kecamatan Cililin, Kabupaten Bandung Barat - Nana Sudiana (Jurnal ALAMI : Jurnal Teknologi Reduksi Risiko Bencana, 2020)
Indonesian territory is a disaster-prone region. There are at least 12 disaster threats that are grouped in geological disasters (earthquakes, tsunamis, volcanoes, landslides), hydrometeorological disasters (floods, flash floods, droughts, extreme weather, extreme waves, forest and land fires), and anthropogenic disasters (epidemics of disease outbreaks and failed technology-industrial accidents). Landslides or land movements in Indonesia in recent years have increased in intensity and frequency. One of the efforts to reduce the risk of landslides that has been carried out by the Disaster Risk Reduction Technology Center-BPPT is to build an Landslide Early Warning System in Jatiradio Village, Cililin District, West Bandung Regency. In order to uniform the implementation of an early warning system for landslides or land movements in disaster prone areas, the government has established a national standard namely SNI 8235: 2017 on the Early Warning System for Land Movements. The purpose of this study is to evaluate the compliance between the Landslide Early Warning System that has been developed by PTRRB-BPPT with the Indonesian National Standard for the Land Movement Early Warning System (SNI 8235: 2017). Based on the results of data analysis and evaluation, it can be concluded that the implementation of the landslide early warning system in Jatiradio Village, Cililin Village, Cililin District, West Bandung Regency is in accordance with the Indonesian National Standard (SNI 8235: 2017) concerning the Soil Movement Early Warning System.